(3GdeUGQa hTQcGJ GdJCejf GdJLGQjIs - (3eLjO LGSe(B, (3GdTQYs ((3YeGf(B:s (3LGeYI ajdGOdajG(B,s, 2003)
(3GdeMGSHI aj GdeUGQa GdJYQja HGdeUGQa hCfTWJgG GdeNJdaI(B- (3GdYedjGJ GdNGUI HJOGhd GdfbO hGdhOGFY hGdChQGb GdJLGQjI(B- (3GdYedjGJ GdNGUI HGdChQGb GdeGdjI hGdMhdGJ GdeUQajI hGdEYJeGOGJ(B- (3GdeWGHbI GdjhejI ddYed GdeUQaj(B- (3EYOGO GdbhGFe GdeGdjI(B- (3GdeMGSHI aj TQcGJ GdJCejf(B- (3GdfXGe GdeMGSHj aj TQcGJ GdJCejf(B-(3GdeMGSHI Yf fTGW GdJCejf Ydi GdMjGI(B- (3GdeMGSHI Yf fTGW aQhY GdJCejfGJ GdYGeI(B- (3GdMSGHGJ GdNJGejI hGdJbGQjQ GdeGdjI(B.s
(3cTGa eUWdMGJ U(B.451s
Keywords: (3GdeMGSHI GdJMdjdjIs; (3GdeUGQas; (3TQcGJ GdJCejfs